Karakteristik Dosismetri dari Sektor Kolimator Gamma Knife Perfexion - Jhon Wesly Manik; Eko Hidayanto; Heri Sutanto (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2017)
This study was conducted to evaluate the dosismetry of sector 1-8 collimator 4 mm, 8 mm, 16 mm for the dose rate of Gamma Knife Perfexion. The measurement method for determining the dosimetry of sectors 1-8 is done by calculating the dose rate using chamber ionization detector by convert to Electromter. For calculating the dose rate of each collimator size 4 mm, 8 mm, 16 mm using rules from American Association of Physicists in Medicine Task Grup 51. The dosimetry of the sectors 1 to8 in the 4 mm, 8 mm, and 16 mm 4, 42.46%, 97.35%, 126.16%Keywords: Gamma Knife Perfexion, Elektrometer, Detector Ionisasi Chamber Dosimetri Gamma Knife, AAPM TG 51